Respuesta :
Answer:
[tex]\sum_{n=0}^\infty (1/20) (-1)^n(\frac{x-21}{20})^n[/tex]
Step-by-step explanation:
Remember the geometric series
[tex]\frac{a}{1-x} = \sum_{n=0}^{\infty} ax^n[/tex]
So we can express
[tex]f(x) = \frac{1}{x-1} = \frac{1}{x-1+21-21} \\=\frac{1}{(x-21)+20} \\= \frac{1}{ \frac{20}{20}( (x-21) +20 )} \\= \frac{1/20}{1+(\frac{x-21}{20}) } \\\\= \frac{1/20}{1-(-\frac{x-21}{20}) } \\\\\\= \sum_{n=0}^\infty (1/20) (-\frac{x-21}{20})^n\\= \sum_{n=0}^\infty (1/20) (-1)^n(\frac{x-21}{20})^n[/tex]
The ith term of the Taylor polynomial is: [tex]\mathbf{ \sum\limits^{\infty}_0 \frac{1}{20} (-1)^i(\frac{x-21}{20})^i }[/tex]
The function is given as:
[tex]\mathbf{f(x) = \frac{1}{x -1}}[/tex]
And the Taylor polynomial is centered at: [tex]\mathbf{x = 21}[/tex]
Rewrite f(x) as:
[tex]\mathbf{f(x) = \frac{1}{x -1 + 0}}[/tex]
Express 0 as 21 - 21
[tex]\mathbf{f(x) = \frac{1}{x -1 + 21 - 21}}[/tex]
This gives
[tex]\mathbf{f(x) = \frac{1}{x + 20 - 21}}[/tex]
Rewrite as:
[tex]\mathbf{f(x) = \frac{1}{x - 21+ 20 }}[/tex]
Multiply f(x) by 1
[tex]\mathbf{f(x) = \frac{1}{x - 21+ 20 } \times 1}[/tex]
Express 1 as 20/20
[tex]\mathbf{f(x) = \frac{1}{(x - 21)+ 20 } \times \frac{20}{20}}[/tex]
Rewrite as:
[tex]\mathbf{f(x) = \frac{1/20}{((x - 21)+ 20 )\times \frac{1}{20}} }[/tex]
Expand
[tex]\mathbf{f(x) = \frac{1/20}{\frac{x - 21}{20}+ 1 } }[/tex]
Apply associative property
[tex]\mathbf{f(x) = \frac{1/20}{1 + \frac{x - 21}{20} } }[/tex]
Express + as --
[tex]\mathbf{f(x) = \frac{1/20}{1 -(- \frac{x - 21}{20} )} }[/tex]
Recall that the sum to infinity of a geometric progression is:
[tex]\mathbf{\sum\limits^{\infty}_0 ar^n = \frac{a}{1- r}}[/tex]
By comparison:
[tex]\mathbf{a = \frac{1}{20}}[/tex]
[tex]\mathbf{r = -\frac{x-21}{20}}[/tex]
So, we have:
[tex]\mathbf{\sum\limits^{\infty}_0 \frac{1}{20} \times ( -\frac{x-21}{20})^n = \frac{a}{1- r}}[/tex]
Split
[tex]\mathbf{\sum\limits^{\infty}_0 \frac{1}{20} \times (-1)^n \times (\frac{x-21}{20})^n = \frac{a}{1- r}}[/tex]
Rewrite as:
[tex]\mathbf{\frac{a}{1- r} = \sum\limits^{\infty}_0 \frac{1}{20} \times (-1)^n \times (\frac{x-21}{20})^n }[/tex]
Replace n with i
[tex]\mathbf{T(i) = \sum\limits^{\infty}_0 \frac{1}{20} \times (-1)^i \times (\frac{x-21}{20})^i }[/tex]
[tex]\mathbf{T(i) = \sum\limits^{\infty}_0 \frac{1}{20} (-1)^i(\frac{x-21}{20})^i }[/tex]
Hence, the ith term is: [tex]\mathbf{ \sum\limits^{\infty}_0 \frac{1}{20} (-1)^i(\frac{x-21}{20})^i }[/tex]
Read more about Taylor polynomials at:
https://brainly.com/question/23842376